Computation of Moments in the Anisotropic Plane Elasticity Fast Multipole formulation - Dias Junior, Afonso (2017)
In this work we will present the computation of moments in the anisotropic plane elasticity fast multipole formulation. Fundamental solutions of plane elasticity are represented by complex functions from the classical 2D elasticity theory. The Multipole Expansion for kernels U (displacement field) and T (traction field) will be computed using Taylor series expansion. The convergence of the series expansion to the fundamental solutions is analyzed considering different numbers of series terms and different distance from the source point to the field point. Moments will be used to evaluate integrals of inï¬‚uence matrices when elements are far away from the source point, whereas the conventional approach will be applied to evaluate the integrals in order to compare results obtained by the multipole expansion.